A Customer-Centered Smart Charging Strategy Considering Virtual Charging System - Mokhtar, Mohamed (2022)
Electric vehicle (EV) charging is considered as one of the main issues that face EV drivers. Thus, there should be a facility to suggest the best charging station based on the customer requirements. However, the routing process of EVs in most of the literature was generally implemented centrally based on the charging station/operator perspective. On contrary, this paper proposes a smart charging strategy that routes EVs drivers to the best charging station based on their priorities. In the proposed smart strategy, various charging stations will cooperate through a virtual charging system (VCS) to serve all EVs charging requests with a high satisfaction level. The drivers’ requirements are achieved through a new scoring criterion which ranks the participating charging stations based on EV driver’s perspective. Then, the EV driver will select individually the charging station based on his priorities. The data required for the scoring criterion are computed through two stages: offline (day-ahead) and online stages. The expected waiting time at each charging station within the VCS is computed during the offline stage based on the forecasted arrivals. The integration between offline and online stages aims to reduce the data flow, calculated data, and finally the communication bandwidth during the online stage. Different case studies are introduced to evaluate the significance of the proposed strategy. The results demonstrate the superiority of the proposed strategy in achieving EVs requirements.